Haemoproteus minutus is highly virulent for Australasian and South American parrots - Ortiz-Catedral, Luis; Braun, Michael P.; Wink, Michael (Parasites & vectors, 2019)
Haemoproteus and Plasmodium species are widespread avian blood parasites. Several Plasmodium species are known for their high virulence and have caused significant declines in naïve bird populations. The impact of closely related Haemoproteus parasites is largely unknown. Recently we reported a lethal disease in two parrot aviaries caused by Haemoproteus parasites.